Accurate Identification of Leishmania Parasites in Sandflies by Polymorphism Analysis of COII Gene Using PCR and qPCR-HRM Techniques in Iranian Border with Iraq - Seyedeh Maryam Ghafari; Reza Fotouhi- Ardakani; Parviz Parvizi (Tehran University of Medical Sciences, 2023)
Background: Firmly identification of Leishmania in Phlebotomus papatasi and understanding of natural transmission cycles of parasites in sandflies are important for treatment and local control. Methods: Modified and developed method of High Resolution Melting (HRM) as a preferable technique was employed to accurate identification of Leishmania in sandflies from Iranian border with Iraq, by targeting cytochrome oxidase II (COII) gene and designing suitable primers. PCR products cloned into pTG19-T vector, then purified plasmid concentration was measured at 260 and 280 nm wavelength. The melting curve plots were generated and DNA sequences were analyzed using Sequencher 3.1.1, CLC Main Workbench 5.5, MEGA 6, DnaSP5.10.01 and MedCalc® version 13.3.3 soft wares. Results: Among about 3000 collected sandflies, 89 female P. papatasi were identified and two with L. major. In amplified fragment of COII gene among 611 bp, 452 bp had no genetic variations with low polymorphic sites (P=0.001) and high synonymous (79.8%) as compare to non-synonymous sites (20.2%). L. major was discriminated in P. papatasi with 0.84 °C Tm and unique curve based on thermodynamic differences was an important criteria using HRM technique. Conclusion: Subsequent war in Iraq made a high risk habitat for parasites transmission. It is important to discover accurate diagnostic procedures for leishmaniasis control.